2016
DOI: 10.1016/j.jclepro.2016.03.127
|View full text |Cite
|
Sign up to set email alerts
|

Liquid fertilizer products from anaerobic digestion of food waste: mass, nutrient and energy balance of four digestate liquid treatment systems

Abstract: This study compared four different digestate liquid treatment systems of a theoretical anaerobic digestion plant in order to facilitate the utilization of municipal food waste nutrients in agriculture. The mass, nutrient and energy balances of a theoretical plant digesting 60 kt/y of food waste were used to evaluate the feasibility of the treatments to concentrate nutrients into liquid fertilizer products. The studied technologies for digestate liquid treatment were ammonia stripping, ammonia stripping combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(77 citation statements)
references
References 46 publications
2
62
0
9
Order By: Relevance
“…This trend was recorded for elements such as nitrogen, phosphorus, potassium, magnesium, manganese, iron, zinc, aluminium and copper. Therefore, these digestates can be said to be rich in nutrient and has great potentials to increase both the microbial and nutrient status of soil when applied through the rhizosphere as fertilizers especially in nutrient-depleted soils (Tampio et al, 2016a). Plant growth and general wellbeing could also be enhanced via the use of such digestate as biofertiliser especially in Sub-Saharan Africa and other regions faced with soil nutrient depletion and erosion of top soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend was recorded for elements such as nitrogen, phosphorus, potassium, magnesium, manganese, iron, zinc, aluminium and copper. Therefore, these digestates can be said to be rich in nutrient and has great potentials to increase both the microbial and nutrient status of soil when applied through the rhizosphere as fertilizers especially in nutrient-depleted soils (Tampio et al, 2016a). Plant growth and general wellbeing could also be enhanced via the use of such digestate as biofertiliser especially in Sub-Saharan Africa and other regions faced with soil nutrient depletion and erosion of top soil.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic digestion is a biochemical process that is widely used for the treatment and energy recovery from many kinds of biomasses, especially agricultural products and agro-industrial wastes (He et al, 2016;Othman et al, 2017). It is an efficient method which employs diverse microbial groups for the conversion of biomasses and wastes into biogas (which serves to mitigate the energy challenges currently faced in several parts of the world) (Ismail and Talib, 2016;Chuichulcherm et al, 2017) and digestate biofertilizer which can be used to improve soil nutrients and plant growth when applied either in solid or liquid form (Shane and Gheewala, 2017;Tampio et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a feasible utilization method ought to be adopted to enrich nutrient concentrations and reduce the volume of digested slurry so that the pre-treated digested slurry could be easily transported and applied as a fertilizer in regions of high demand [9]. This nutrient enrichment and mitigation strategy might also help reduce the environmental pollution risk of nutrient run-off and leaching by the surplus application of digested slurry [10].…”
Section: Introductionmentioning
confidence: 99%
“…The physical‐chemical methods include struvite formation , ammonia stripping , evaporation , membrane separation , adsorption processes with activated carbons, ion exchange resins, zeolites , and biochar , as well as various combination of these processes. In particular, Tampio et al have shown that the system based on evaporation combined with reverse osmosis is an efficient nutrient technology for the production of transportable fertilizer products for agricultural application due to the highest concentration of nutrients, nutrient availability, the low mass of the product and low energy consumption of the treatment. Stripping is an efficient technology for nitrogen recovery; however, the high mass of the residue containing the remaining K and P should be further managed sustainably.…”
Section: Introductionmentioning
confidence: 99%